Mosquito Larvacidal Activity of Zingiber montanum Rhizome Extract Against Aedes aegypti larvae - Dwi Sulistia Ningrum; Siwi Pramatama Mars Wijayanti; Kuswanto Kuswanto (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2019)
Aedes aegypti is the main vector which transmits Dengue virus as causing agent of Dengue Haemmorhagic Fever (DHF). Chemical control of Ae. aegypti have an impact on the environment and humans, also burden a high cost. One of the efforts to reduce the negative impact of synthetic insecticide, which is to find out alternative natural insecticide from plant-based insecticides. The purpose of this research is to determine the killing power of the rhizome bangle extract to Ae. aegypti larvae. This research was a quasi-experimental design with post test only control group design. The concentration of extract rhizome bangle used were 0%; 0.125%; 0.25%; 0.5%; 0.75% and 1%. The mosquito sample used in this study were instar III of Ae. aegypti larvae as many as 600 larvae. Data analysis used univariate and bivariate (probit and Kruskal Wallis test). The results showed that there was an effect of the concentration of extract rhizome bangle against the mortality of Ae. aegypti larvae with p=0,002 (p<0,05). Extract rhizome bangle effectively killed Ae. aegypti larvae with LC50 and LC90 were 0.148 % and 0.338 %, with the most effective concentration is 1%. Based on this research, extract rhizome bangle has a larvicidal effect on Ae. aegypti, so it can be used as an alternative method to minimize the usage of chemical larvicides that easily applied by the community.